Framing theory application in public relations: the lack of dynamic framing analysis in competitive context - Kuan, Duan; Mohd Hasan, Nurul Ain; Mohd Zawawi, Julia Wirza; Abdullah, Zulhamri (SAGE Publications, 2021)
This study reviews the literature that uses Framing theory in recent international public relations studies. It aims to overview the research status of Framing theory in public relations and the highlighted core knowledge and voids from scholarly literature. The method used in this study is a systematic literature review, which involves pre-set criteria in selecting academic articles to be surveyed within ten years (1 January 2010 to 31 December 2019) and qualitative synthesis of the findings. A systematic search was conducted related to framing, Framing theory, and international public relations in three databases namely Web of Science, ProQuest Central, and Scopus. These databases contain literature with framing applications in public relations. The main findings reveal that Framing theory was applied with dynamic framing analysis in PR is still weak.